INTERVENÇÃO PEDAGÓGICA COM ABORDAGEM CTS/CTSA, NA PERSPECTIVA FREIREANA, NA EDUCAÇÃO DE JOVENS E ADULTOS: UM CAMINHO PARA O EXERCÍCIO DA CIDADANIA - Gava, Jéssica Endringer Dias (2021)
Currently, we live with many environmental, social, economic and political changes as a result of scientific and technological discoveries. This contributes, in many aspects, to the improvement of human life, but it can have serious consequences for nature. Therefore, we need to understand the risks and benefits that these scientific advances provide to society and minimize their harmful effects on the environment. Therefore, it is necessary to create means that allow the construction of social values, aimed at nature conservation, in which related themes can be worked on in schools, in an interdisciplinary and cooperative manner, valuing the historical and cultural context of students, especially individuals included in Youth and Adult Education (YAE). YAE is composed of a diverse audience, with people who did not complete their studies in the proper time, for various reasons, and who, in their majority, have learning difficulties, in addition to being unaware of many scientific concepts, although in their daily lives , experience its real meaning. This research is based on the Freirean perspective, with the objective of investigating whether the pedagogical intervention, in Youth and Adult Education, with the STSE approach, worked in an interdisciplinary and contextualized way, is able to enable a more integrative knowledge in the school environment. Being essential the use of an increasingly comprehensive dialogue in the teaching-learning process. It is classified as a qualitative, bibliographical research, which identifies, in the available literature, how the STSE movement is approached and worked, also as a case study, which used Pedagogical Interventions to collect raw data, anchored by the instruments : dialogue circles, workshops on the preparation of soap from used oils, recipes for reusing food peels and encouraging healthy eating, application of a semistructured questionnaire and a forum. The results obtained were categorized a posteriori by the content analysis of Bardin (2016). This analysis of the categories allowed us to reflect on the importance of bringing teaching-learning tools to schools that can make students analyze the environmental, social and economic reality, critically and with prominence, contributing to exercise their citizenship.